Self-efficacy and Resilience as Mediators in the Relationship between Test Anxiety and Spiritual Intelligence among High School Students in Qom - Mohammad Ali Jamshidi; Malihe Fadaei Moghadam; Sakineh Ghorbani; Mohammad Farhoush (Shahid Beheshti University of Medical Sciences, 2017)
For downloading the full-text of this article please click here. Background and Objective: Spiritual intelligence is effective in reducing test anxiety which hinders academic performance. Discovering mediating variables in the relationship between spiritual intelligence and test anxiety paves the way for developing suitable training packages in order to reduce test anxiety. The aim of this study was to investigate the mediating role of self-efficacy and resilience in the relationship between spiritual intelligence and test anxiety. Method: This descriptive study was of correlational type and its research population was all high school students in Qom in 1395 and 1396. Random cluster sampling was used. To do so, three female and three male schools were randomly selected and 380 questionnaires were distributed in some classes and then collected. 269 questionnaires (127 boys and 142 girls) were acceptable. The participants completed test anxiety questionnaire (Sarason, 1997), SQ (Abdollahzadeh, 2009) and Efficacy (Sherer, 1982) and Resiliency (Connor & Davidson, 2003). As for data analysis, Pearson correlation and path analysis based on Baron and Kenny model were used. In this study, the ethical issues were all considered and the authors declared no conflict of interest. Results: Pearson correlation analysis showed that test anxiety and spiritual intelligence (0/267), efficacy (-0/475) and resilience (-0/330) have a significant relationship (P<0/01). Moreover, the results of path analysis indicated that efficacy (0/17) and resilience (0/09) completely mediate the relationship between spiritual intelligence and test anxiety. Conclusion: Based on the findings, spiritual intelligence reduces test anxiety through self-efficacy and resilience. Thus, it is proposed that spiritual intelligence training packages with an emphasis on raising students' self-efficacy and resilience be developed to reduce test anxiety. For downloading the full-text of this article please click here.